Respuesta :
Perform what's inside the brackets first
"2(x-3)+2" ---> 2x-6+2 ---> simplify (add the 2 and the -6 together) ---> 2x-4 ---> put your simplified version back into the brackets ---> [2x-4]
Now multiply your 3 with whatever is in the brackets to get rid of the brackets
"3[2x-4]"
6x-12
Do the same with the 5 and whatever is still in parenthesis after the 5
"5(x-3)"
5x-15
Add the two simplified terms together
"6x-12+5x-15"
combine the like terms ---> 6x+5x=11x and -12(+)-15=-27
Put your two answers back into one equation
"11x-27"
And that is your final answer
"2(x-3)+2" ---> 2x-6+2 ---> simplify (add the 2 and the -6 together) ---> 2x-4 ---> put your simplified version back into the brackets ---> [2x-4]
Now multiply your 3 with whatever is in the brackets to get rid of the brackets
"3[2x-4]"
6x-12
Do the same with the 5 and whatever is still in parenthesis after the 5
"5(x-3)"
5x-15
Add the two simplified terms together
"6x-12+5x-15"
combine the like terms ---> 6x+5x=11x and -12(+)-15=-27
Put your two answers back into one equation
"11x-27"
And that is your final answer